Support for Early Childhood to Develop Social Skills: Project Method in Learning Process What is the Impact? - Nurhidayah, Siti; Syamsudin, Amir; Damayanti, Alfina (Yayasan Nurul Yakin Bunga Tanjung, 2025)
The development of social skills in early childhood can be achieved through learning activities with project-based learning methods. This study aims to determine the effect of the project method on children's socialization skills in Izzatin Lahat Kindergarten group B1. This type of research is quantitative and uses a pre-experimental research method. The research design used is the group Pretest- Posttest Design which invites a total of 12 children aged 6 years. The sampling technique uses purposive sampling and the data collection technique uses observation, tests, and documentation. Data analysis in testing the research hypothesis uses the t-test. The results of the study showed that there was a difference or positive influence of the project method treatment in learning children's socialization skills on children's socialization skills, this can be seen together the results of two pre-tests had an average score of 38.3 and the results of two post- tests after being given treatment had an average score of 74.5, and the results of the project method on children's socialization skills obtained Fcount < Ftable (2.83 < 2.98). This can be proven by the t-count value = 46.268, which is greater than the t-table value = 2.178 because the t-count value > t-table (46.268 > 2.178), then H0 is rejected, and Ha is accepted. This study provides information that the project method has a positive effect on socializing skills, especially in children in group B1 at Izzatin Lahat Kindergarten